PENGARUH KERAGAMAN PRODUK DAN FREE SHIPPING TERHADAP KEPUTUSAN PEMBELIAN KONSUMEN SHOPEE (Studi Mahasiswa Politeknik Kotabaru) - Andriansyah; Muhdar; Rosida (Program Magister Ilmu Administrasi Bisnis FISIP Universitas Lambung Mangkurat, 2024)
This research aims to determine the effect of product diversity and free shipping on consumer purchasing decisions. The location of this research was carried out at the Kotabaru Polytechnic. This research used a quantitative approach. The samples taken in this study were 50 people using saturated sampling techniques. The results of this research show that there is an influence of product diversity and free shipping on consumer purchasing decisions on the Shopee online buying and selling site at Kotabaru Polytechnic.